Technical graphics communication - Bertoline, Gary R. (McGraw-Hill, 2003)
In its third edition, Technical Graphics Communication, has become a standard in the field of engineering and technical graphics. This text presents both traditional and modern approaches to technical graphics, providing engineering and technology students with a strong foundation in standard drafting practices and techniques.